Pengaruh Multinasionalitas, Tax Haven, Dan Goodwill Terhadap Transfer Pricing Dengan Moderasi Political Connection - Kristianto, Anggelica Yufa; Sumaryati, Anna (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
Transfer pricing is a critical issue as global trade allows multinational companies to operate across borders. Despite the increased tax revenue associated with transfer pricing, Indonesia's economy is negatively affected. This study aims to assess how multinational practices, tax haven use and goodwill have affected the transfer pricing trends of multinational companies. This study used secondary data from annual reports of multinationals listed on the Indonesia Stock Exchange. Energy companies from the aforementioned stock exchange were selected using an intentional sampling method from 2018-2022. The quantitative analysis applied the multiple regression technique, and the research sample comprised 21 companies. SmartPLS version 3 tool was utilized to analyze the gathered data. The results show that tax havens have a positive and significant effect on transfer pricing. There is no detectable effect of multinationality or goodwill. The importance of political connections in the tax haven/transfer pricing nexus highlights its critical moderating role.